Here comes the sun - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Here comes the sunso-called renewable energies, solar, wind, biomass, you may be tempted to ask 'which is the fairest of them all?'. Well, first get some definitions sorted out, because most of them are solar energy, when you think about it.Solar...